Records of the Kosciusko Huts Association - Kosciusko Huts Association; Schlink, Herbert H. (Herbert Henry), 1883-1962.; Snowy Mountains Hydro-electric Authority (1926)
MS 7335 incorporates the papers of Sir Herbert Schlink and comprises correspondence, 1927-1955, including correspondence relating to Kosciusko Ski developments and facilities and the development of a Snowy Mountains Authority. Photographs, including opening of Schlink Pass, early days and Hotel Kosciusko. Publications, including A day's skiing on the Muniong Ranges; Australian ski year book (published on behalf of the Ski Council of New South Wales), no. 1 (1928)-no. 4 (1931); Skiing from Kiandra to Kosciusko July 28-30, 1927 (published by Sydney Mail, 31 August 1927). Snowy Mountains Authority records, 1954-1955, including leaflets, illustrated booklet, list of publications and map. Miscellaneous press cuttings, 1923-1977. Department of Lands 1925 map of the Snowy Mountains, Kosciusko and Kiandra districts. Bookplates (1 box).
Manuscript reference no.: MS 7335.
Associated materials: Records of the Kosciusko Huts Association, 1970-2009 MS 8257, MS Acc09.197.
Sir Herbert Schlink (1883-1962) was a gynaecologist, surgeon and hospital administrator who played a leading part in the development of Australia's snowfields. Schlink Pass, the highest road pass in Australia, opened on 29 April 1961, was named after him. Schlink was involved in the first Kiandra to Kosciuszko ski tour, 1927.
The Kosciusko Huts Association, formed in 1971, is an Australia-wide organisation which restores and maintains huts in the Kosciuszko and Namadgi National Parks for use by bushwalkers and skiers. The Association also undertakes research into the historic significance of the Parks' huts.
Keywords: Schlink, Herbert H. -- 1883-1962 -- Archives; Kosciusko Huts Association -- Archives; Mountain shelters -- New South Wales -- Kosciuszko National Park; Skis and skiing -- New South Wales -- Kosciuszko National Park; Hiking -- New South Wales -- Kosciuszko National Park; Kosciuszko National Park (N.S.W.)